Impact Of Data Mining In The Era Of Electronic Data Management In Digital Examination System With Support For Knowledge-Driven Decisions (International Journal of Food and Nutritional Sciences, 2022)
Due to the availability of a vast amount of educational information that can be obtained from various sources, EDM has attracted a significant amount of attention from scholars over the past few decades. The primary purpose of EDM is to make DM models more effectively in order to protect the vast quantities of educational information and to develop an environment that is conducive to the safety of the student's educational pursuits. Within the framework of this strategy, a variety of models have been implemented for DM and its analytics. In addition, prediction models such as classification, regression, and latent factor evaluation technologies were utilised in the analysis process.